Role of digital health insurance management systems in scaling health insurance coverage in low- and Middle-Income Countries: A case study from Nigeria - Okey Okuzu; Ross Malaga; Kenneth Okereafor; Ujulu Amos; Afolabi Dosunmu; Abiodun Oyeneyin; Victor Adeoye; Mohammed Nasir Sambo; Bassey Ebenso (Frontiers Media S.A., 2022)
BackgroundIncreasing global commitment to Universal Health Coverage (UHC) in the past decade has triggered UHC-inspired reforms and investments to expand health service coverage in many Low- and Middle-Income Countries (LMICs). UHC aims to ensure that all people can access quality health services, safeguard them from public health risks and impoverishment from out-of-pocket payments for healthcare when household members are sickAimThis paper reviews the role of health insurance as a policy tool to address health financing as a contributory mechanism for accelerating the achievement of UHC in LMICs. We focus on Nigeria's legal framework for health insurance coverage for its whole population and the role of technology in facilitating enrollment to health insurance schemes.MethodsFrom May to July 2022, we adopted a cross-sectional case study design combining: (i) a literature review of the effects of UHC with (ii) document analysis of health insurance systems in Nigeria, and (iii) secondary analysis of health insurance datasets to understand experiences of deploying MedStrat, a locally-developed digital health insurance management system, and its features that support the administration of health insurance schemes in multiple states of Nigeria. We drew on contemporary technology adoption models to triangulate diverse data analyzed from literature and documents reviews and from health insurance datasets to identify: (i) enablers of adoption of digital insurance schemes, (ii) the contribution of digital technology to expanding access to health insurance, and (iii) further scalability of digital insurance intervention.ResultsPreliminary findings suggests that digital insurance management systems can help to increase the number of enrollees for insurance especially among poor households. Three contextual enablers of adoption of digital insurance schemes were a favourable policy environment, public-private-partnerships, and sustained stakeholder engagement and training.Discussion and conclusionKey elements for successful scaling of digital health insurance schemes across Nigeria and similar contexts include: (i) ease of use, (ii) existing digital infrastructure to support electronic insurance systems, and (iii) trust manifested via data encryption, maintaining audit trails for all data, and in-built fraud prevention processes. Our findings affirm that digital health technology can play a role in the attainment of UHC in LMICs.